Evaluation of ophthalmic and hemodynamic parameters in capuchin monkeys (Sapajus sp.) submitted to dissociative anesthetic protocols - Raposo, A. C. S.; Ofri, R.; Schaffer, D. P. H.; Gomes Júnior, D. C.; Libório, F. A.; Martins Filho, E. F. [UNESP]; Oriá, A. P. (Wiley-Blackwell, 2015)
Dissociative drugs are used for chemical restraint in monkeys. The aim was to evaluate muscle relaxation, recovery, and ophthalmic and hemodynamic parameters in 24 capuchin monkeys subjected to four dissociative anesthesia protocols. Animals were anesthetized with tiletamine-zolazepam (TZ), ketamine-xylazine (KX), ketamine-midazolam (KM), or ketamine-dexmedetomidine (KD). Muscle relaxation, digital reflex, lacrimal production, intraocular pressure (IOP), heart and respiratory rates, oxygen saturation (SpO2 ), rectal temperature, non-invasive arterial blood pressure, palpebral and pupillary reflexes, and eyeball positioning were evaluated every 5 minutes for 20 minutes. Muscle relaxation was highest in KM and KD. At 5-minute post-injection, IOP was higher in TZ than in all other groups. There was a significant difference between groups and times in heart and respiratory rates and temperature. There were no significant differences in SpO2, arterial blood pressure, and lacrimal production between groups. The established parameters may help in clinical and ophthalmic examinations of primates.
Keywords: Dexmedetomidine; Intraocular pressure; Ketamine; Lacrimal production; Midazolam; Tiletamine-zolazepam; Xylazine